Covid-19 Quarantine: Impact of Lifestyle Behaviors Changes on Endothelial Function and Possible Protective Effect of Beetroot Juice - Volino-Souza, Mônica; Oliveira, Gustavo Vieira de; Conte-Junior, Carlos Adam; Alvares, Thiago Silveira (Frontiers in Nutrition, 2020)
The current recommendation for reducing person-to-person Coronavirus 2019 (COVID-19) transmission is social distancing, including remote work and school, and home confinement. However, confinement may cause negative feelings, such as frustration, anger, boredom, and stress, in quarantined people. Furthermore, unhealthy diet and physical inactivity behaviors are commonly linked to home confinement, leading to weight gain, metabolic disorders, smoking, and exacerbated alcohol consumption. As a result, these unhealthy behaviors are typically linked to vascular endothelium damage (endothelial dysfunction), which is a first step for the development of cardiovascular disease (CVD). Given that CVD is the main cause of morbidity and mortality worldwide, attenuating the progression of endothelial dysfunction is very important for the control of CVD. Consuming vegetable rich in nitrate, such as beetroots, may be an effective way to prevent endothelial dysfunction. Several emerging studies have recommended beetroot juice in order to improve endothelial function in hypertensive, hypercholesterolemic individuals, as well as in those with CVD risk factors. Therefore, nitrate-rich vegetable consumption, such as beetroot, should be encouraged to be included in the diet during confinement from COVID-19 outbreaks in order to alleviate the potential negative effect of home confinement on cardiovascular health.